2020
DOI: 10.1016/j.tics.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Neurobiology of Interoceptive Inference

Abstract: What is the function of the insular cortex? Two recent studies (Gehrlach et al. and Livneh et al.) offer new insight into how this enigmatic brain region integrates interoception and exteroception in the service of emotion. The findings provide much needed causal evidence for the nascent theory of interoceptive inference. Two recent studies by Gehrlach et al [1] and Livneh et al [2] shed new light on the function

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 9 publications
9
86
0
Order By: Relevance
“…Confirming our initial hypotheses, patients with PTSD displayed increased SN connectivity with the bilateral anterior insula/frontal operculum, the right temporal pole, and the left SMC at baseline as compared to healthy individuals. This pattern of “pathological connectivity” in the PTSD group is strongly supported by the current knowledge base ( Lanius et al, 2011 , Wang et al, 2016 , Akiki et al, 2017 , Fenster et al, 2018 , Vanasse et al, 2019 ), where such disruptions in SN connectivity have been shown to be associated with PTSD symptoms of hyperarousal, hypervigilance, avoidance, and altered interoception ( Sripada et al, 2012 , Tursich et al, 2015 , Yehuda et al, 2015 , Akiki et al, 2017 , Harricharan et al, 2019 , Allen, 2020 , McCurry et al, 2020 , Nicholson et al, 2020a ). The temporal pole is a paralimbic region that is highly interconnected with the amygdala and orbitofrontal cortex and is involved in both sensory and limbic processing of emotional states ( Olson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Confirming our initial hypotheses, patients with PTSD displayed increased SN connectivity with the bilateral anterior insula/frontal operculum, the right temporal pole, and the left SMC at baseline as compared to healthy individuals. This pattern of “pathological connectivity” in the PTSD group is strongly supported by the current knowledge base ( Lanius et al, 2011 , Wang et al, 2016 , Akiki et al, 2017 , Fenster et al, 2018 , Vanasse et al, 2019 ), where such disruptions in SN connectivity have been shown to be associated with PTSD symptoms of hyperarousal, hypervigilance, avoidance, and altered interoception ( Sripada et al, 2012 , Tursich et al, 2015 , Yehuda et al, 2015 , Akiki et al, 2017 , Harricharan et al, 2019 , Allen, 2020 , McCurry et al, 2020 , Nicholson et al, 2020a ). The temporal pole is a paralimbic region that is highly interconnected with the amygdala and orbitofrontal cortex and is involved in both sensory and limbic processing of emotional states ( Olson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the SN decodes innate alarm system signals in the context of threatening stimuli, detecting and integrating both emotion and sensory information ( Lanius et al, 2017 , Szeszko and Yehuda, 2019 ). Critically, alterations within the SN have been linked to PTSD symptoms of hyperarousal, hypervigilance, avoidance, and altered interoception ( Sripada et al, 2012 , Tursich et al, 2015 , Yehuda et al, 2015 , Akiki et al, 2017 , Harricharan et al, 2019 , Allen, 2020 , McCurry et al, 2020 , Nicholson et al, 2020a ). Individuals with PTSD often display elevated SN connectivity during rest, particularly to anterior subregions of the insular cortex, with less connectivity to emotion regulation areas in the dlPFC ( Sripada et al, 2012 , Lanius et al, 2015 , Koch et al, 2016 , Harricharan et al, 2019 , Jeong et al, 2019 , Nicholson et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…This selective role in memory consolidation of TFC is also supported by anatomical studies showing that the pIC is a candidate for the integration of viscerosensory inputs (Allen, 2020;Livneh et al, 2020) as well as for the convergence of both conditioned stimulus (CS, i.e., tone) and unconditioned Stimulus (US, i.e., footshock), resulting from multisensory afferences of thalamic nuclei, as well as from the lateral and basolateral nuclei of the amygdala (Gehrlach et al, 2020;McDonald & Jackson, 1987;Shi & Cassell, 1998a;. Although there seems to be a consensus in the literature that the IC is not necessary for the acquisition of fear conditioning -since manipulations before training have shown no effect (Brunzell & Kim, 2001;Gehrlach et al, 2019;Lanuza et al, 2004) -it is possible that the pIC is preferably recruited to consolidate and maintain the association between a discrete stimulus (i.e., tone) and the US, which would explain the selective effect observed with post-training inactivation of the pIC in our study.…”
Section: Discussionmentioning
confidence: 53%
“…The insula (or insular cortex, IC) has been implicated in a myriad of functions such as emotion regulation, cognition, interoception, homeostasis and salience processing (Allen, 2020;Benarroch, 2019;Gogolla, 2017;Nieuwenhuys, 2012;Uddin, 2015;Uddin et al, 2014Uddin et al, , 2017. Animal studies have further revealed a key role for the IC in aversive states (Gehrlach et al, 2019;Méndez-Ruette et al, 2019), multimodal processing and integration of visceral and somatosensory inputs (Livneh et al, 2017(Livneh et al, , 2020Rodgers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…), the study of ‘interoception’ (or the brain’s processing of sensory inputs from within the body) has begun receiving attention only relatively recently 1 . While theoretical concepts of the dynamic interplay of brain and body – including interoception, homeostatic and allostatic control 25 – exist, empirical investigations have lagged behind. However, empirical studies of interoception have been recently boosted by a surge of interest in multiple neuroscientific fields, given that impairments in interoceptive processing have been proposed to play a role in emotions, decision making, consciousness and mental health 1,6 .…”
Section: Introductionmentioning
confidence: 99%